LINGUISTIC INTERPRETATION OF THE CONCEPT OF” BEAUTY " AND THE EXPRESSION OF GENDER ETHALON IN IT - Marufova Zulfiya Nabievna (Galaxy International Interdisciplinary Research Journal, 2021)
The article mentions the interpretation of the concert “beauty” in artistic works, studies conducted by linguists on this subject. Also, the issue of gender identity in the expression of beauty is analyzed by the example of Uzbek artistic written literature.